Biochemical, Antioxidant, and Antimicrobial Profiling of Essential Oils of Indian Origin for Culinary Applications - K. Sathish Kumar; S. Visnuvinayagam; G. Teena; K. Elavarasan; J. Bindu; Amjad K. Balange; R. Sivaranjani; L. Narasimhamurthy (International Journal of Food Science)
This study investigated the biochemical composition and tested the antioxidant and antimicrobial properties of four Indian-origin essential oils (EOs)—ginger, garlic, clove, and eucalyptus—to evaluate their potential for culinary applications. Gas chromatography–mass spectrometry (GC–MS) analysis was used to identify the chemical constituents of EOs. Antioxidant assays such as 2,2-diphenyl-1-picrylhydrazyl (DPPH) and ferric reducing antioxidant power (FRAP) and antimicrobial assays such as Agar well diffusion, minimum inhibitory concentration (MIC), and minimum bactericidal concentration (MBC) were carried out. In GC–MS analysis, α-zingiberene (28.01%), eugenol (70.12%), 1,8-cineole (52.95%), and allyl polysulfides and terpenes were the most dominant compounds in ginger, clove, eucalyptus, and garlic EOs, respectively, which are responsible for their antioxidant and antimicrobial properties. Based on the antioxidant assays, clove EO exhibited the strongest antioxidant activities in both DPPH 70.84±3.95% and FRAP (142.29±1.05 μ mol Fe (II) g−1) even at 5% level, suggesting its potential to inhibit lipid peroxidation, a process linked to oxidative stress in food. The antimicrobial study demonstrated the potential of EOs against foodborne pathogens, particularly against methicillin-resistant S. aureus (MRSA), which reveals their potential against multidrug-resistant bacteria. Among them, clove EO demonstrated the most potent antimicrobial activity against both Gram-negative and Gram-positive bacteria, with notable activity against MRSA with an inhibition zone of 41.33±0.57 mm. This strong antimicrobial activity of clove EO was directly correlated with its total phenolic content (375.91±14.21 mg phenols 100 g−1 at 5% level). The results indicated that clove EO stands out for its strong antioxidant and antimicrobial properties, particularly against multidrug-resistant pathogens like MRSA. These findings suggest clove EO could be a promising natural alternative to synthetic preservatives and antibiotics in culinary applications, helping to preserve food and combat resistant bacteria.